Study of Economic Impacts of Lockdown on Small Businesses in the city of Pune, Maharashtra, India - Sayli Bapat; S.R. Kandalgaonkar; Bhagyashree Deshpande; Jyoti Harchekar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The year 2019-20 has been very challenging for the entire world. The impact of the pandemic, the virus name COVID -19 has an unpredictable and serious impact of the lockdown on small trade and business. The small business man and the trader, whose lively hood is depended on the daily work or daily income bases, showing their concern about the survival in the pandemic situation, many of the small businesses were restricted due to social distancing and have to shift their businesses according to the demand of the urgent need of people and earning. This paper provides the analysis of the impact of the lockdown situation on the small businesses in the city of Pune. Over all the paper contributes to our understanding of the monetary impact of COVID - 19 on the common people.